Pengaruh Pola Asuh Uninvolved terhadap Kecanduan Merokok di Kalangan Remaja di Desa Karanggayam - Uswatun Hasanah; Maghfiroh Izzani Maulania (Universitas Islam Tribakti Lirboyo Kediri, 2025)
The phenomenon of juvenile delinquency leading to nicotine addiction among adolescents is a primary concern, especially in Karanggayam Village. This study aims to analyze the influence of uninvolved parenting style on smoking addiction among adolescents. This parenting style is characterized by low parental responsiveness and involvement, which can negatively impact an adolescent's emotional development and self-control. This issue is based on the high prevalence of active smokers (90%) among adolescents in Karanggayam Village, Srengat District, Blitar Regency. This research uses a quantitative approach with a sample of 44 adolescents. The data were analyzed using a simple linear regression test. The results show that the uninvolved parenting style has a significant and positive influence on smoking addiction in adolescents. This influence contributes 53.6%, while the rest is influenced by other factors outside of this study. The findings of this research prove a strong relationship between the uninvolved parenting style and smoking addiction. These findings can serve as an important basis for parents and policymakers to develop more effective prevention programs